Isoflavones from black chickpea (Cicer arietinum L) sprouts with antioxidant and antiproliferative activity - Dulce-María, Domínguez-Arispuro (Saudi J Biol Sci, 2021)
Black chickpea is a good source of bioactive compounds, particularly isoflavones. Sprouting improves nutraceutical value in chickpea seeds. This study aimed to explore the role of sprouting of black chickpea seeds on the synthesis of isoflavones and evaluate the impact of the soluble isoflavone on cellular antioxidant activity (CAA) and antiproliferative activity in breast cancer cells. Isoflavones were identified and quantified by HPLC-UV-MS. The CAA and antiproliferative activity were determined in HepG2 cells and MDA-MB-231 cancer cells, correspondingly. In sprouted black chickpea, six isoflavones (formononetin, biochanin-A, and its glycosides) were identified and the total isoflavones content increased (0.31 to 35.72 µgBA/mg of extract). The CAA was increased five times from 137.2 to 788.2 µMEQ/100 g of sample. The bioactive compounds in sprouted chickpea decreased the proliferation of MDA-MB-231 cell line. Also caused morphological changes such as cell shrinkage, rounding and nuclear fragmentation. The results herein suggest that bioactive compounds, as isoflavones, in sprouted black chickpea showed a potential antioxidant and antiproliferative activity. Therefore, it may be considered as a value-added product or ingredient for produce functional foods.